Beyond negative attitudes: Examining HIV/AIDS stigma behaviors in clinical encounters. Issue 11 (2nd November 2017) - Varas-Díaz, Nelson; Rivera, Marinilda; Rivera-Segarra, Eliut; Neilands, Torsten B.; Ortiz, Nerian; Pedrogo, Yasmín; Mendoza, Sigrid; Rivera Amador, Andrés; Martínez García, Stephanie; Rivera Suazo, Sugeily; Albizu-García, Carmen E.
ABSTRACT: HIV/AIDS related stigma remains a major global health issue with detrimental consequences for the treatment and health of people with HIV/AIDS (PWHA), especially when manifested by health professionals. Research on HIV/AIDS stigma has successfully documented negative attitudes towards PWHA among health professionals. However, fewer studies have examined how stigma is manifested behaviorally by health professionals during clinical interactions. Therefore, this study aimed to: (1) examine the behavioral manifestations of HIV/AIDS stigma among physicians in training during clinical interactions, and (2) document the interrelation between HIV/AIDS stigma attitudes and behaviors. We implemented an experimental design using Standardized Patient (SP) simulations, observational techniques, and quantitative questionnaires. The sample consisted of 66 physicians in training in Puerto Rico who engaged in SP encounters with two scenarios: (1) PWHA infected via illegal drug use (experimental condition), and (2) a person with a common cold (control condition). Results evidenced statistically significant differences between both simulations ( p = .047), with a higher number of stigma behaviors manifested in the experimental condition. HIV/AIDS stigma attitudes were not correlated with stigma behaviors. Negative emotions associated with drug use were positively associated with drug-related stigmatizing behaviors.